Diseminasi Pemulihan Pariwisata Dengan Penerapan Chse Di Kampung Wisata Mangrove Monro-Monro - Husain, Fahrisal; Amirullah, Amirullah; Hakim, Maksud; Anugrah Manippi, Wahyu; Hasbul, Wahyuni; Suryadi, Andi Fitriani (STMIK Royal, 2023)
Abstract: Monro-Monro Mangrove Tourism Village is an area located in Monro-Monro Village, Binamu District, Jeneponto Regency. This tourist village is expected to be able to increase people's income by utilizing tourist visits. Restrictions on community activities during a pandemic resulted in the tourism sector experiencing obstacles. The government finally issued a tourist guide, namely Cleanliness, Healthy, Safety and Environmentally Sustainable, namely ISO 9024: 2021 standardized tourism recovery guidelines. This community service activity is related to public awareness of the importance of a guideline that is carried out by tourism managers in welcoming tourists. The program being carried out is dissemination which seeks to increase public understanding and tourism awareness groups regarding cleanliness, health, safety and environmental sustainability, as tourist rights. This activity was carried out using observation, training, mentoring, evaluation and output methods. The target of counseling is the tourism awareness group (Pokdarwis). It is hoped that increased knowledge and understanding of CHSE will make it easier to realize tourism recovery in terms of increasing tourist visits. The results of the dissemination carried out gained the enthusiasm of tourism-aware residents to increase their understanding of Sapta Pesona in the CHSE guidelines. Keywords: Dissemination; CHSE Guidelines; Tourism recovery; Pokdarwis Abstrak: Kampung Wisata Mangrove Monro-Monro merupakan Lingkungan yang berada di Kelurahan Monro-Monro Kecamatan Binamu Kabupaten Jeneponto. Kampung wisata ini diharapkan mampu meningkatkan pendapatan masyarakat dengan memanfaatkan kunjungan wisatawan. Pembatasan kegiatan masyarakat pada saat pandemic mengakibatkan sektor wisata tersebut mengalami hambatan. Pemerintah akhirnya mengeluarkan panduan wisata yaitu Cleanliness, Healthy, Safety dan Enviroment Sustainable yaitu pedoman pemulihan wisata terstandardisasi ISO 9024:2021. Kegiatan pengabdian kepada masyarakat ini terkait kesadaran masyarakat akan pentingnya suatu pedoman yang dijalankan pengelola wisata dalam menyambut wisatawan. Program yang dijalankan adalah diseminasi yang berupaya meningkatkan pemahaman masyarakat dan kelompok sadar wisata terkait kebersihan, kesehatan, keamanan serta kelestarian lingkungan, sebagai hak wisatawan. Kegiatan ini dilaksanakan dengan metode pengamatan, pelatihan, pendampingan, evaluasi dan output. Target penyuluhan mengambil sasaran yaitu kelompok sadar wisata (Pokdarwis). Diharapkan dengan meningkatnya pengetahuan dan pemahaman tentang CHSE akan mempermudah dalam mewujudkan pemulihan pariwisata dalam hal kunjungan wisatawan yang semakin meningkat. Hasil dari diseminasi yang dilaksanakan mendapatkan antusiasme warga sadar wisata peningkatan pemahaman sapta pesona dalam pedoman CHSE. Kata kunci: diseminasi; pedoman chse; pemulihan pariwisata; pokdarwis